AlGaN/GaN HEMTs on Si by MBE with regrown contacts and fT = 153 GHz. Issue 3 (20th March 2014) - Ganguly, Satyaki; Song, Bo; Hwang, Wan Sik; Hu, Zongyang; Zhu, Mingda; Verma, Jai; Xing, Huili (Grace); Jena, Debdeep
Abstract: AlGaN/GaN high‐electron‐mobility transistors (HEMT) have been grown by radio frequency molecular beam epi‐taxy (RF‐MBE) on 3″ Si substrates. A record low contact resistance Rc ˜ 0.11 Ω.mm has been achieved for GaN HEMTs on Si by using non alloyed ohmic contacts regrown by MBE. Owing to the low contact resistance a 75‐nm gate length unpassivated HEMT shows intrinsic current gain cut‐off frequency fT =153 GHz, a high saturation drain current density> 1.3 A/mm and a low RON of 1 Ω.mm, among the best reported for HEMTs on Si. With further scaling GaN HEMTs on Si can compete in the high‐performance RF arena with similar devices on SiC, while exploiting the many advantages of integration with Si. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)